Tea beverage in chemoprevention and chemotherapy of prostate cancer - Siddiqui Imtiaz A; Saleem Mohammad; Adhami Vaqar M; Asim Mohammad; Mukhtar Hasan (Acta Pharmacologica Sinica; Vol 28, No 9 (September 2007): Acta Pharmacologica Sinica（Special Issue on molecular targets, biomarkers and animal models for anti-cancer pharmacological research: potentials and challenges from chemoprevention to chemotherapeutic treatment）, 2016)
Prostate cancer (PCa) is the most frequently diagnosed malignancy and the second leading cause of cancer-related deaths in American males with similar trends in many western countries. The existing treatment approaches and surgical intervention have not been able to effectively cope with this dreaded disease. For these reasons, it is necessary to intensify our efforts for a better understanding of the disease process and for the development of novel approaches for its prevention and treatment. Based on considerable evidence from in vivo and in vitro data and epidemiological studies, in recent years the beverage tea has gained considerable attention for reducing the risk of several cancers. Much of the cancer preventive effects of tea, especially green tea appear to be mediated by the polyphenols present therein. Geographical evidence suggests that the incidence and occurrence of PCa is lower in populations that consume tea regularly. This evidence suggests that tea polyphenols could be extrapolated to optimize their chemopreventive properties against PCa. PCa represents an excellent candidate disease for chemoprevention because it is typically diagnosed in men over 50 years of age and therefore, even a modest delay in neoplastic development achieved through pharmacological or nutritional intervention could result in a substantial reduction in the incidence of clinically detectable disease. In this review we address the issue of possible use of tea, especially green tea, for the prevention as well as treatment of PCa.